Radiographically occult perforation and dissection of the common carotid artery following stab injury to the neck. (June 2017) - Gamba, Sebastian; Lachat, Mario; Alkadhi, Hatem; Simmen, Hans-Peter; Jensen, Kai Oliver
Abstract: In recent years, many diagnostic algorithms have been devised to reduce the rate of negative explorations associated with indiscriminate surgical management of penetrating neck injuries. In hemodynamically stable patients, the need for surgical intervention is usually determined by integrating both clinical signs and radiological findings; if such investigations remain unremarkable, recommended treatment consists in close observation and sequential physical examinations. We report on a 29-year-old male who was admitted to a Swiss tertiary care hospital after sustaining a penetrating injury to his left neck following a knife attack. Disregarding a pre-hospital account of hemorrhage from the wound and slight dysphagia, no manifest symptoms or signs of internal organ damage were present on primary survey. Moreover, there was no evidence of vascular or aerodigestive tract injury on initial CT angiography. We nonetheless proceeded with immediate surgical exploration, exposing a significant perforation of the left common carotid artery with concomitant dissection of the said vessel. Surgical repair was successfully performed and the patient suffered no long-term sequelae. We thus recommend that a high level of suspicion be upheld in both asymptomatic and oligosymptomatic patients with PNI and that clinical practitioners remain cautious in the face of deceptively reassuring radiologic findings.